(untitled) (Research, Society and Development, 2024)
This article aims to address the serious climate crisis faced by Amazonas due to the severe drought predicted for 2024. A descriptive and exploratory study is carried out, with a qualitative approach and methodological procedure of the case study, unique type. Climate change, intensified due to deforestation and the emission of greenhouse gases, have caused significant changes in precipitation and temperature patterns in the region, leading to profound socio-environmental impacts. Riverine, indigenous and quilombola communities face difficulties such as lack of drinking water, loss of biodiversity and increase in diseases. The government of Amazonas, together with national and international organizations, has implemented emergency measures to mitigate the effects of the drought and promote the resilience of affected populations, to minimize the impacts of the drought in Amazonas and the mitigation strategies adopted, highlighting the urgent need to effective and sustainable public policies to guarantee the preservation of natural resources and quality of life in the Amazon.